2021
DOI: 10.32478/ajmie.v2i1.702
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Direct Corrective Feedback in Improving Students' Writing Performance and Motivation at MTs YP KH Syamsuddin Ponorogo

Abstract: This research is aimed to foster students’ motivation in improving writing performance by implementing direct corrective feedback. Direct error correction identifies both the error and the target form. Providing corrective feedback is an essential part of language learning because it influences students’ learning and achievement. Feedback helps both teachers and students to meet their goals in teaching and learning. Feedback and motivation are two perceptions which control the students’ English as foreign lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…al., (2014) concluded that written corrective feedback provided a guide for students to correct their mistakes. Studies have also indicated that WCF helped improve students' writing performance and served as a positive motivation in the writing process (Agustiningsih & Andriani, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…al., (2014) concluded that written corrective feedback provided a guide for students to correct their mistakes. Studies have also indicated that WCF helped improve students' writing performance and served as a positive motivation in the writing process (Agustiningsih & Andriani, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This includes crossing out unwanted words or words wrongly used as well as adding the missing content left out in the writing. Agustiningsih and Andriani (2021) found that the implementation of direct corrective feedback showed improvement in students' writing performance and served as a positive motivation in the writing process. Syu et.…”
Section: Types Of Corrective Feedbackmentioning
confidence: 95%
See 1 more Smart Citation